Real-world risk of brain metastases in stage III non-small cell lung cancer in the era of PET and MRI staging - Alhusaini, Saud; Lanman, Tyler A.; Ko, Ryan B.; Therkelsen, Kate E.; Eyben, Rie Von; Diehn, Maximilian; Soltys, Scott G.; Pollom, Erqi L.; Chin, Alexander; Vitzthum, Lucas; Wakelee, Heather A.; Padda, Sukhmani K.; et al. (Frontiers in Oncology, 2023)
Objective: The 2-year incidence of brain metastases (BrMs) in stage III non-small lung cell cancer (NSCLC) has been estimated to be around 30%. However, recent clinical trials have demonstrated considerably lower BrMs rates in this patient population. In this study, we aimed to review the real-world incidence, surveillance, and treatment patterns of BrMs in stage III NSCLC. Materials and Methods: Using a retrospective single-center study design, we identified patients with stage III NSCLC who received radiation with curative intent over a 10-year period. Outcome variables included BrMs incidence, overall survival (OS), and survival from date of BrMs. Additionally, we assessed patterns of BrMs surveillance in stage III NSCLC and treatment. Results: We identified a total of 279 stage III NSCLC patients, of which 160 with adequate records were included in the final analyses [adenocarcinoma (n = 96), squamous cell carcinoma (n = 53), other histology subtype (n = 11)]. The median OS for the entire cohort was 41 months (95% CI, 28-53), while the median time from BrMs to death was 19 months (95% CI, 9-21). Twenty-three patients (14.4%) received planned surveillance brain MRIs at 6, 12, and 24 months after completion of treatment. The remaining 137 patients (85.6%) received brain MRIs at systemic recurrence (restaging) or when neurologically symptomatic. A total of 37 patients (23%) developed BrMs, with a 2-year cumulative BrMs incidence of 17% (95% CI, 11-23). A higher incidence of BrMs was identified in patients with adenocarcinoma relative to those with squamous cell carcinoma (p < 0.01). Similarly, a higher 2-year BrMs incidence was observed in patients who received planned surveillance brain MRI relative to those who did not, although statistical significance was not reached. Stereotactic radiosurgery (SRS) treated 29 of BrMs patients (78.4%) and was preferred over WBRT, which treated only 3 patients (8.1%). Conclusions: At our center, BrMs incidence in stage III NSCLC patients was lower than historically reported but notably higher than the incidence described in recent clinical trials. Routine BrMs surveillance potentially allows earlier detection of asymptomatic BrMs. However, asymptomatic BrMs were mostly detected on restaging MRI at the time of recurrence.